1954
DOI: 10.1017/s002531540000357x
|View full text |Cite
|
Sign up to set email alerts
|

The nervous control of luminescent responses in polynoid worms

Abstract: Some preliminary observations on luminescence in polynoid worms have been presented in a previous paper (Nicol, 1953). These animals produce light in scales (elytra) which cover the dorsal surface of the body. The source of the light lies in a layer of unicellular epithelium on the lower surface of the scale. Histologically, this tissue consists of columnar cells (photocytes), characterized by the presence of coarse eosinophilic granules in the cytoplasm. The nervous supply of the elytrum derives from a nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

1954
1954
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…However, because of its ubiquity, the specific mode, level and site of action of acetylcholine in the bioluminescent process remain unclear. Muscarinic cholinergic and serotoninergic mechanisms have been described in benthic scale-worms (Polynoïdae) as part of the excitatory pathway of elytral luminescence (Nicol, 1954;Nicolas et al, 1978;Miron et al, 1987;Anctil et al, 1989). The tube-worm Chaetopterus variopedatus (Chaetopteridae) produces a glowing blue mucus in response to the contractile action of the adjacent epithelio-muscular cells, which are controlled by muscarinic cholinergic and GABAergic pathways (Nicol, 1952;Anctil, 1981;Martin and Anctil, 1984;Anctil, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…However, because of its ubiquity, the specific mode, level and site of action of acetylcholine in the bioluminescent process remain unclear. Muscarinic cholinergic and serotoninergic mechanisms have been described in benthic scale-worms (Polynoïdae) as part of the excitatory pathway of elytral luminescence (Nicol, 1954;Nicolas et al, 1978;Miron et al, 1987;Anctil et al, 1989). The tube-worm Chaetopterus variopedatus (Chaetopteridae) produces a glowing blue mucus in response to the contractile action of the adjacent epithelio-muscular cells, which are controlled by muscarinic cholinergic and GABAergic pathways (Nicol, 1952;Anctil, 1981;Martin and Anctil, 1984;Anctil, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…an area of the epithelium of the lower face ( Fig. 1) emits flashes of light upon stimulation (Nicol 1953(Nicol , 1954(Nicol , 1957a(Nicol ,b,c, 1958. The behavioural function of this bioluminescence remains unknown, and the hypothesis that the signal could be a warning or distracting one has not been demonstrated.…”
Section: Luminous Scales and Photosomesmentioning
confidence: 99%
“…Temporal characteristics are similar to those recorded in a previous section (latency, 13-21 msec; duration, ca. 100 msec; rise time, 26-30 msec) (Nicol, 1953). Consecutive flashes show facilitation (Nicol, 1954).…”
Section: Electrical Stimulation Of Isolated Elytra (Narcosis-free)mentioning
confidence: 99%
“…I) 261 Earlier studies (Nicol, 1953(Nicol, , 1954 showed that two kinds of luminescent responses are produced by electrical stimulation of isolated polynoid scales, viz. brief flashes and a long-lasting glow, the latter frequently being brighter.…”
mentioning
confidence: 99%